الأساليب الإنشائية في سورة الزمر دراسة بلاغية تحليلية - صوالح احميمة, بدر الدين; قزي, عصام (University of Eloued-جامعة الوادي, 2022)
"في اللغة العربية قواعد ما بين نحوية وبلاغية وغير ذلك, وكلُّها قطعة واحدة متماسكة وفيها ما يعرف بالأساليب وهي الطريقة التي يعبِّر بها كل متكلم، ويتوقف فهم كلام الله تعالى على فهم الأسلوب الذي جاء به عز وجل, ولأجل هذا كان اختيارنا لفهم الأساليب التي جاء بها القرآن الكريم وذلك من خلال سورة الزمر. وكان البحث بعنوان: الأساليب الإنشائية في سورة الزمر- دراسة بلاغية تحليلية – وهو يحاول الإجابة على الإشكال التالي: مَا صِيَغُ الأَسَالِيبِ الإِنْشَائِيَّةِ اَلْمَوْجُودَةِ فِي سُورَةِ الزُّمَر وَمَا أَنْوَاعُهَا وَمَا غَايَاتُهَا الْبَلَاغِيَّة ؟، وقد تطرقنا لمعالجة هذا الإشكال من خلال كلام المفسرين وعلماء البلاغة في معرفة أنواع وصيغ الأساليب الإنشائية ودلالة كل صيغة، واتبعنا المنهج التحليلي الاستنتاجي في تقرير أنواع وأشكال ودلالات الأساليب الإنشائية في سورة الزمر، وكانت النتائج كالتالي: اعتماد السورة الكريمة على الأساليب الإنشائية الطلبيّة فقط دون الأساليب غير الطلبية التي لم نجدها فيها، وقد شَكَّلَ أسلوب الاستفهام في السورة ظاهرة تلفت النظر في كثرتها عند مقارنتها بالأساليب الإنشائية الأخرى، فهو يُعَدُّ الأسلوب الأكثر وروداً في السورة. ""Abstract: In the Arabic language there are rules between grammatical, rhetorical, and other things, all of which are one coherent piece, and in it there is what is known as the styles, which is the way in which each speaker expresses. And that through Surat Al-Zumar, and the research was entitled: Structural methods in Surat Al-Zumar - a rhetorical and analytical study - and it poses the answer to the following problem: What are the formulas of the existing construction methods in Surat Al-Zumar, and its meanings and interpretations are addressed through this statement? Interpreters and scholars of rhetoric in knowing the types and forms of construction styles and the significance of each formula, and we followed the analytical-deductive approach in deciding the types, forms, and connotations of construction styles in Surat Al-Zumar, and the results were as follows: The reliance of the noble surah on obligatory construction methods only without the non-required methods because they do not exist in them. The questioning style in the surah was a phenomenon that draws attention to its abundance when compared to other construction methods, as it is considered the most frequent method in the surah. "
مذكرة ماستر
Keywords: الأساليب الإنشائية، سورة الزمر، القرآن الكريم، بلاغة، الاستفهام، النداء، الأمر، النهي، التمني، الأغراض البلاغية; Structural methods, Surat Az-Zumar, the Noble Qur’an, eloquence, interrogation, appeal, command, prohibition, wishful thinking, rhetorical purposes